75 Transgender Patients (Hair Transplantation, 2023)
Transgender patients pursue hair restoration surgery with the goal of reshaping their existing hairline to match their preferred gender identity. Follicular unit transplantation allows the patient to have a hairline and hairstyle that most appropriately fit the gender with which they identify. There are several studies that demonstrate that gender reassignment surgery is highly satisfying for this patient population. Most transgender hair transplants involve the male-to-female patients who desire to lower their hairline, round the frontotemporal angles, and increase density in the midscalp, ultimately creating a natural, feminine appearance. Depending on the extent of hair loss, one of the most challenging aspects of hair restoration for the transgender female patient is the amount of donor hair available for the hair transplant versus the degree of androgenetic alopecia that has affected the individual. The surgeon must completely analyze the patient’s facial features, skin color, hair characteristics, and degree of hair loss in developing a realistic treatment plan. Options for lowering the hairline for the transgender female include follicular unit transplantation and surgical hairline advancement. Less commonly, transgender male patients seek to masculinize their appearance by transplanting hair to the beard, goatee, mustache, and chest.
Keywords: transgender; gender dysphoria; gender identity; gender identity disorder; transgender male; transgender female; male-to-female; female-to-male